2020
DOI: 10.3389/fphys.2020.545184
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Within the Nucleus Ambiguus Inhibits Gastrointestinal Motility in Rats

Abstract: Hydrogen sulfide (H 2 S) is a neuromodulator in the central nervous system. However, the physiological role of H 2 S in the nucleus ambiguus (NA) has rarely been reported. This research aimed to elucidate the role of H 2 S in the regulation of gastrointestinal motility in rats. Male Wistar rats were randomly assigned to sodium hydrosulfide (NaHS; 4 and 8 nmol) groups, physiological saline (PS) group, capsazepine (10 pmol) + NaHS (4 nmol) group, L703606 (4 nmol) + NaHS (4 nmol) group, and pyrrolidine dithiocarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Capsazepine was also found to inhibit NaHS-induced pyloric smooth muscle relaxation, indicating that the effect of H 2 S donors on enhancing gastric emptying and inducing pyloric sphincter relaxation is mediated by the activation of TRPV1 receptors. Although there are many mechanisms by which this effect can be manifested, our data support the theory of smooth muscle relaxation induced by afferent neuronal TRPV1 receptor activation[ 45 , 60 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Capsazepine was also found to inhibit NaHS-induced pyloric smooth muscle relaxation, indicating that the effect of H 2 S donors on enhancing gastric emptying and inducing pyloric sphincter relaxation is mediated by the activation of TRPV1 receptors. Although there are many mechanisms by which this effect can be manifested, our data support the theory of smooth muscle relaxation induced by afferent neuronal TRPV1 receptor activation[ 45 , 60 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our experiments revealed that the injection of the NF-κB pathway blocker PDTC followed by NaHS eliminated the modulation of gastric function by NaHS. H 2 S is mainly synthesized in the brain by the CBS enzyme, andwe found that NaHS injection in both the ambiguous and paraventricular nuclei inhibited gastric motility in rats via the NF-κB pathway[ 44 , 45 ], that the injection of NaHS to the brain blocked inflammation-associated apoptosis, and that treatment with NaHS reduced the expression of inflammatory factors in astrocytes and microglia due to Alzheimer’s disease[ 46 ]. H 2 S reduces the levels of phosphorylated p38 MAPK and phosphorylated p65 NF-κB in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also acts in a dose-dependent manner in appropriate physiological concentrations (10-130 μM) Moshal et al (2008). We also observed inhibition of gastric motility in the rats after exogenous H 2 S donor NaHS was injected in the NA Sun et al (2020). Therefore, we suggest that H 2 S can modulate gastric function through the NMDA receptors, but within the normal physiological concentration range.…”
Section: Discussionmentioning
confidence: 54%